The Determinants of Racial Differences in Parenting Practices - Thompson, Owen (Journal of Political Economy, 2018)
Blacks and whites in the United States adopt widely different parental behaviors, but the underlying causes of these differences are not well understood. This paper documents large-scale increases in cognitively stimulating parenting among southern black mothers who came of age in the period immediately following the civil rights movement. The total magnitude of these improvements was approximately 0.5 standard deviations between the 1957 and 1964 birth cohorts, while no significant trends occurred among blacks outside of the South or among whites from any region.